Increased morphological variation and a new record of Vanilla labellopapillata (Orchidaceae) from the Mato Grosso State, Brazil - Engels, Mathias Erich; Dias, Daianny Correia; Koch, Ana Kelly (Phytotaxa, 2020)
Vanilla labellopapillata is reported for the first time from the state of Mato Grosso, in the Southern Brazilian Amazon. This rare species is currently known only from a handful of specimens collected in the Central and Oriental Amazon. Based on the new collection, both the geographical range and morphological variation of V. labellopapillata increase significantly. We present an updated description, taxonomic and ecological comments, geographic distribution data, illustrations in line drawing and photographs.